End-to-end pairwise key establishment using node disjoint secure paths in wireless sensor networks. (19th March 2007) - Ling, Hui; Znati, Taieb
Resource aware random key predistribution schemes have been proposed to overcome the limitations of energy constrained Wireless Sensor Networks (WSNs). In most of these schemes, each sensor node is loaded with a key ring. Neighbouring nodes are considered to be connected through a secure link if they share a common key. Nodes which are not directly connected establish a secure path which is then used to negotiate a symmetric key. However, since different symmetric keys are used for different links along the secure path, each intermediate node must first decrypt the message received from the upstream node. Notice that during this process, the negotiated key is revealed to each node along the secure path. The objective of this paper is to address this shortcoming. To this end, we propose an end-to-end pairwise key establishment scheme which uses a properly selected set of node disjoint paths to securely negotiate symmetric keys between sensor nodes. We show through analysis and simulation that our scheme is highly secure against node captures in WSNs.